Réponses

2014-03-05T17:07:08+01:00
A)(1+√5)² = 1² + √5² =1+5 =6
b)(3+√2)² =3²+√2² =9+2 =11
c)(√3 -5)² =√3² -5² = 3-25 = -22
d)(7-√11)²= 7²-11= 49-11 = 38

e) (√6+2) (√3-√2) = Je sais plus comment on fais ni pour le f)
  • Utilisateur Brainly
2014-03-05T17:13:33+01:00
Développer et réduire:

A= (1+√5)²
A= 1 + 2√5 + 5
A= 6 + 2√5

B= (3+√2)²
B= 9 + 6√2 + 2
B= 11 + 6√2

C= (√3-5)²
C= 3 - 10√3 + 25
C= 28 - 10√3

D= (7-√11)²
D= 49 - 14√11 + 11
D= 60 - 14√11

E= (√6+2) (√3-√2)
E= 3√2 - 2√3 + 2√3 - 2√2
E= √2

F= (
5+2) (10-1)
F= 5
√2 - √5 + 2√5 - √2
F= 4√2 + √5

Voilà! :)